Applying some lemmas and theorems in calculating limits - Abdusalom Khakimov; Sanakul Abjalilov; Dilfuza Ashurova; Tolibova Zarina (Genius Journals, 2025)
The article considers the issues of facilitating the process of calculating the limits of some non-standard sequences and functions using linear permutations, lemmas and theorems. Also, applications of calculating the limits of some sequences and classes of functions using simple permutations to theoretical and practical problems are presented.
Keywords: Sequence; function; limit theory; linear permutations